(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The rapid rise of e-commerce has significantly impacted traditional markets. Society is faced with two choices: to embrace the progress of the time or not. This service project explores the challenges sellers face in Semarang’s Karangayu Market face due to shifting consumer behavior towards online shopping. The declining income and customer base prompted a community service project by Universitas Widya Husda Semarang to equip sellers with online sales strategies. The program targeted 18 sellers dealing in fashion products. It involved three phases: survey, implementation, monitoring, and evaluation. The program addressed challenges by presenting the evolution of online shopping and popular e-marketplace platforms, providing a question-and-answer session where participants expressed concerns about e-marketplace competition. Conducting a training session on creating Shopee seller accounts, highlighting the functionalities of the Shopee seller dashboard for managing online stores. The community service team initiative successfully empowered sellers with basic e-marketplace knowledge and skills. Regular training programs targeting non-digital sellers are recommended to bridge the digital divide and ensure the sustainability of traditional markets. This program can serve as a model for future initiatives aimed at supporting traditional businesses in the digital era.